Analysis Of Budget Preparation Methods In The Population And Civil Registration Service Of Nias Regency - Zai, Kurniawan Sarototonafo; Hulu, Tri Hartati Sukartini; Waruwu, Noviza Asni; Bu'ulolo, Nanny Artatina (Journal of Management, Economic, and Accounting, 2025)
Recognizing the importance of the budget in determining the activities to be implemented within the agency, it is crucial to prepare a detailed budget to avoid underfunding or overspending in carrying out these activities. With a budget, each function within the agency, particularly the Nias Regency Population and Civil Registration Office, has the necessary work services to carry out activities as outlined in the budget for a specific period. The purpose of this study is to determine the budget preparation process implemented by the Nias Regency Population and Civil Registration Office. The title of this study is "Budget Preparation Methods at the Nias Regency Population and Civil Registration Office." Based on the results of the analysis and evaluation conducted by the researcher, it can be concluded that a well-designed and detailed budget will yield positive results in activity implementation. Therefore, the researcher recommends that budget preparation at the Nias Regency Population and Civil Registration Office continue to adhere to the budget preparation process established by the government.